Observations on non-random distribution of spores of Henneguya spp. (Cnidaria: Myxosporea: Myxobolidae) within plasmodia - Eiras, Jorge C; Cruz, Manuel; Cruz, Cristina; Saraiva, Aurelia; Adriano, Edson A; Szekely, Csaba; Molnar, Kalman (Folia parasitologica, 2017)
Species of the cnidarian genus Henneguya Thélohan, 1892 (Myxosporea: Myxobolidae) are histozoic parasites commonly found in freshwater and, more rarely, in marine fish. The development of these parasites in fish tissues includes the formation of plasmodia within which occurs the sporogony originating spores with two caudal processes, which are usually randomly distributed within the plasmodia. In this report the authors present some cases of non-random distribution of the spores of six species of Henneguya within their plasmodia. Two different patterns of non-random distribution were found based on a literature survey. These patterns and their origin are discussed. Apparently this non-random distribution of the spores is due to both internal and external factors.
Keywords: Parasitic Diseases, Animal; parasites; Myxozoa; spores arrangement; motility; nemoci ryb; Fishes; Animals; Fish Diseases; Gills; žábry; parazitární nemoci u zvířat; spory; Spores; zvířata; fish; ryby